Autolytic enzymes in hyphae of Aspergillus nidulans: their action on old and newly formed walls. - Polacheck, Y (1975)
Walls, purified from hyphae of the ascomycete Aspergillus nidulans, autolyzed on incubation and liberated glucose, mannose, galactose, N-acetylglucosamine, and soluble oligosaccharides. Digestion proceeded at linear rates until approximately 3% of the wall polymers had been hydrolyzed and then slowed markedly. The change in the rate of autolysis was not due to loss of enzyme activity but was caused by the disappearance of a fraction of the wall which was highly susceptible to digestion. Radioactive labeling showed that this fraction was the newly formed wall. The new wall was highly susceptible to enzyme action both when it was deposited at the apex in growing hyphae or when deposited laterally in hyphae treated with cycloheximide. The relations between wall modification and apical growth are discussed.